USING SCRABBLE GAME IN IMPROVING STUDENTS’ VOCABULARY MASTERY OF SMP NEGERI 1 JAWAI - Yuli Lidiasari; Sofian Sofian; Iwan Supardi (Universitas Tanjungpura, 2017)
AbstractThe research was conducted based on the problems found in teaching and learning process. Students had problem in 2 aspects of vocabulary. They had the difficulties in determining the meaning of words and spelling the word correctly. The purpose of this research was to improve students’ vocabulary mastery by using Scrabble game to the Class VII C students of SMP Negeri 1 Jawai in academic year 2016/2017. The method used in this research is Classroom Action Research which consists of Planning, Acting, Observing, and Reflecting. This research was done in three cycles. The participants of this research were the seventh grade English teacher and 32 students in class VII C. The researcher used observation and measurement test to collect the data. The researcher elaborated the result of observation checklist, field note and students’ mean score in order to get the research findings. The mean score of students’ individual test score improved in each cycle. In the first cycle, the mean score was 64.06 categorized into average, it increased to 78.75 categorized into average to good in the second cycle, and it increased to 92.18 categorized into good to excellent in the third cycle. In conclusion, Scrabble Game improved students’ vocabulary.Keywords: Vocabulary Mastery, Scrabble Game